Implications of the EU-Mercosur Association Agreement for Austria - a preliminary assessment - Franz Sinabell; Julia Gruebler; Oliver Reiter (FIW - Research Centre International Economics, 2020)
This study presents quantitative and qualitative assessments of potential consequences of the trade agreement between the EU and Mercosur countries. It is embedded in a wider Association Agreement and was made public in summer 2019. The focus is on Austria. One objective of the agreement is to liberalise trade and to improve conditions for making investments in order to create jobs and value added and to give consumers in both regions better access to a wide range of products and services. A gravity model analysis shows that average income gains per person are remarkably similar in both regions. However, the economies in Mercosur countries will benefit more than EU Member States economies in relative terms. A second objective of the agreement is to meet targets that go beyond immediate economic benefits, such as to further sustainable development, to prevent environmental deterioration, to avoid social frictions and to smooth adaptation processes. A qualitative comparison shows the advancements compared to other trade agreements and the limitations of trade agreements to address social and environmental concerns. An in depth-appraisal of the provisions for agriculture shows potential benefits and costs for consumers and farmers in both regions.
Keywords: F13; F15; F17; F18; Q17; 330; trade liberalisation; EU; MERCOSUR; gravity model; environment; agriculture